Inverted Cooling Travelling Grate Process - Pilot Scale Evaluation - Rossano Augusto Pilon Nunes; Maycon Athayde; Luis Henrique Torres Dantas (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
The objective of this work is to evaluate the physical quality achieved in the iron ore pellets and the temperature profile in the pellet bed by applying an inversion in the flow during the cooling. The firing of pellets requires a minimum residence time in the sintering temperatures of the hematite grains [1]. The applied concept aims at raising this time to pellets located at the bottom of the bed which would provide an improvement in the physical quality of the product. The tests were carried out in a pot-grate type oven and the samples of fired pellets were divided into three aliquots according to the loading position of the pot termed top, middle and bottom, the pellets were sieved and subjected to physical tests and the compared to conventional indurating flow with the same ores and inputs. It was possible to show an increase of 7 to 8% in the compressive strength of the medium and bottom layers, maintaining the top layer results. The objectives of the research were achieved and the tests will be extended to assess the impacts on the mass and energy balance of the indurating machine and its components.